Health Care Readiness in Management of Preeclampsia/Eclampsia in Ethiopia: Evidence from National Facility-Based Survey - Meazaw MW; Chojenta C; Forder P; Taddele T; Loxton D (Dove Medical Press, 2022)
Maereg Wagnaw Meazaw,1,2 Catherine Chojenta,2 Peta Forder,2 Tefera Taddele,3 Deborah Loxton2 1Federal Ministry of Health, Addis Ababa, Ethiopia; 2Centre for Women's Health Research, School of Medicine and Public Health, College of Health, Medicine and Wellbeing, University of Newcastle, Newcastle, NSW, Australia; 3Health System and Reproductive Health Directorate, The Ethiopian Public Health Institute, Addis Ababa, EthiopiaCorrespondence: Maereg Wagnaw Meazaw, The University of Newcastle, University Drive, Callaghan, NSW, 2308, Australia, Tel +61 402 290 013, Email mulemar12@gmail.comBackground: Early case detection, treatment, and timely referral for better services can significantly reduce the negative outcomes of preeclampsia and eclampsia. However, evidence on health facilities' readiness to provide such services and the associated challenges is limited in Ethiopia. Therefore, this study aimed to assess the readiness of Ethiopian health care facilities to manage preeclampsia and eclampsia.Methods: This study used the 2016 Ethiopia national emergency management of obstetrics and newborn care (EmONC) survey. This survey was a national cross-sectional census of health facilities that provided delivery services. Data on facility infrastructure, equipment and supplies were collected through a facility checklist, and interview health provider experiences. Cross tabulation, summarisation and chi square tests by facility type, location, and management authority were conducted.Results: There were 3804 health facilities included in the survey across all regions of Ethiopia. The majority of facilities (92%) were public/government managed with only 1% of available hospitals located in rural areas. Poor availability of dipsticks for proteinuria tests (55.3%), caesarean sections (7.9%), and ambulance services (18.4%) were reported across health facilities with high variations in terms of facility type, location, and type of managing authority. Diazepam was a widely available anticonvulsant compared with magnesium sulfate (MgSO4), with more available in private for-profit facilities compared with public facilities. Nearly one third of health care providers were not trained to administer MgSO4 intravenously. The result indicated that the chi-square test was statistically significant at P < 0.001.Conclusions and Recommendations: There were notable gaps in readiness of facilities in detection and management of preeclampsia/eclampsia that increase maternal and perinatal mortality in Ethiopia. Therefore, availability of essential supplies, medications, and referrals are required. In addition, refresher training to healthcare providers on screening, diagnosis and management of preeclampsia/eclampsia and continuous supervision should be provided.Keywords: preeclampsia, eclampsia, facility readiness, Ethiopia, EmONC